Effect of magnetic soft phase on the magnetic properties of bulk anisotropic Nd2Fe14B/α-Fe nanocomposite permanent magnets. (30th January 2018) - Li, Yuqing; Yue, Ming; Zhao, Guoping; Zhang, Hongguo
Abstract: The effects of soft phase with different particle sizes and distributions on the Nd2 Fe14 B/ α -Fe nanocomposite magnets have been studied by the micro-magnetism simulation. The calculated results show that smaller and/or scattered distribution of soft phase can benefit to the coercivity ( H ci ) of the nanocomposite magnets. The magnetization moment evolution during magnetic reversal is systematically analyzed. On the other hand, magnetic properties of anisotropic Nd–Fe–B/ α -Fe nanocomposite magnets prepared by hot pressing and hot deformation methods also provide evidences for the calculated results.